Understanding on and Need for Syaria Insurance: A Case Study in Pekalongan, Central Java, Indonesia - Kuat Ismanto (Journal of Accounting and Investment, 2018)
Objective of the study was to explore how much Pekalongan residents understand and need Syaria insurance in Indonesia. The data collection methods were questionnaire and interview. The questionnaires were distributed randomly to 136 samples/ respondents. The interview was conducted to 10 informants in order to elaborate meaning, respondent’s understanding need and response on syaria insurance. The data analysis method was descriptive-qualitative analysis. The findings showed that most respondents had good level of understanding on syaria insurance. Some respondents stated that insurance was “important” while some others stated that it was “very important.” The respondents considered syaria insurance as investment, financial solution, financial security, business requirement, pension plan and future investment. However, the respondents had very basic understanding on syaria insurance. They associated syaria insurance with Islamic-based insurance and non usury (excessive interest). It implied that there is a market for syaria insurance in this city. It is expected that government and companies support development of syaria insurance in Indonesia.